Exploring domestic workers' subjectivities through stories of their personal childcare arrangements - Michaeu, Nisha (Rhodes University, Faculty of Humanities, Department of Psychology, 2021)
Domestic service has long been a major sector of the South African labour market, for black women particularly, who must support their family and children. Existing research has stressed the way in which race, class and gender has shaped the oppressive character of domestic service in South Africa. In this narrative study a new slant is provided on this existing theoretical discussion of domestic labour, one that is focused on exploring the agentic human being beyond 'the servant question'. This study uses narrative interviews with domestic workers in Makhanda/Grahamstown in the Eastern Cape province of South Africa to show how we can expand on potentially limited or constricted passive 'domestic worker identities' and ideas/beliefs about women who do domestic work. A performative and positioning narrative analysis is used to explore the subject positions of domestic workers in their stories about their childcare arrangements. This analysis examines multiple shifting identities and positions that are used by domestic workers in relation to their maternal subjectivity and their audience (here, a white trainee-psychologist esearcher), while highlighting the significance of narrative methodology in making these positions visible. The areas of focus were their history, experience of domestic work, life outside of domestic work, family network/dynamics and personal childcare arrangements. Under these areas of focus the following was analysed: the ways in which the storyteller positioned herself in her narrative, how she compared/contrasted or located herself in relation to the other, claims of identity that were made, what she incorporated or purposefully left out, words and phrases that were chosen, which sections of talk were embellished or elaborated on and appeals that were made to the interviewer (Riessman, 2002). Through exploring the micro-practices of domestic workers' lives the study found that there were various subject positions constructed and used by this group of women. Findings showed that domestic workers positioned themselves actively as breadwinners, good mothers who give their children opportunities that they were not given, nurturers and crafty mothers who secure good care for their children. In contrast to these active subject positions, positions of sacrifice were performed when domestic workers spoke about leaving their young children in the care of another while they worked. The study also found that participants managed complex positions of disappointment and unmet expectations for a better life in the new South Africa by using narratives of resistance and agency. In certain instances, identity appeals were made to the interviewer that they, and other women who do domestic work, are entrepreneurial and creative with their income and possess skills outside of their day-to-day household cleaning jobs. This was interpreted as an attempt to extend the domestic worker identity positioning beyond the traditionally accepted notions of unskilled/uneducated women who do domestic work. In the study this allowed for more subject positions to be taken up in terms of identities and selves, beyond just being a "domestic worker" .
Keywords: Women household employees, Black -- Social conditions -- South Africa; Women household employees, Black -- Social conditions -- South Africa -- Case studies; Women household employees, Black -- Psychology -- South Africa; Day care aides -- South Africa